SCANellome: Analysis of the Genomic Diversity of Human and Non-Human Primate Anelloviruses from Metagenomics Data - Florian Laubscher; Laurent Kaiser; Samuel Cordey (Viruses, 2023)
Anelloviruses are extremely prevalent in the human population and are considered to be commensal parts of the human virome. The best-known member in humans is the Torque teno virus. Recent metagenomic next-generation sequencing investigations have helped reveal the considerable number of species and genotypes from the same genus that can be co-detected within a single individual and that this diversity increases as a function of age during the first months/years of life. As a result, to date, the bioinformatics analysis of this genetic diversity remains complex and constraining for researchers. Here, we present SCANellome, a user-friendly tool to investigate the anellome composition at the genus, species, and genotype levels of samples from metagenomics data generated by the Illumina and Nanopore platforms. SCANellome is based on an in-house up-to-date database that includes all human and non-human primate anellovirus reference sequences available on GenBank and meets the latest classification criteria established by the International Committee on Taxonomy of Viruses.